miR-4295 Promotes the Malignant Progression of Gastric Cancer via Targeting PTEN - Yang, Xiaoyan; Yang, Jing; Tang, Yunlian; Xie, Zhizhong; Zhang, Yang; Lei, Xiaoyong; Gan, Runliang (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Gastric cancer (GC), one of the common clinical malignant tumors of the digestive system, is the fourth most commonly diagnosed cancer and the second lethal cancer worldwide and has the characteristics of high metastasis, fatality, and recurrence rate. This research was conducted to investigate the role and mechanism of miR-4295 in gastric cancer. Methods: The expression capacity of miR-4295 was determined in gastric cancer tissues and its normal tissues by qRT-PCR. PTEN expression level was detected by western blot. SGC-7901 and MGC-803 cell lines were cultured and transfected with miR-4295 or its inhibitor. The effects of miR-4295 on cell proliferation, colony formation, migration, and invasion in vitro were investigated. The mutual effect between miR-4295 and PTEN in 293T cells was explored by luciferase reporter gene assays. Results: The results showed that miR-4295 expression was higher in gastric cancer tissues and cell lines, and the miR-4295 level was significantly negatively associated with the tumor size and distal metastasis of gastric cancer. Notably, up-regulated miR-4295 promoted cell proliferation, migration and invasion in vitro, whereas it led to contrary effects while down-regulating miR-4295 expression. Further mechanism studies displayed that miR-4295 could directly fasten the PTEN 3’UTR and dramatically decrease the level of PTEN in vitro. Conclusion: The findings revealed that miR-4295 could promote gastric cancer cell proliferation, migration and invasion, which might be attributed to targeting PTEN. Our study suggested that miR-4295 might be a potential therapeutic target for gastric cancer.
Keywords: proliferation